METHODOLOGICAL APPROACHES AND CLINICAL RESEARCH METHODS AND REGULATORY ADAPTATION PROCESSES IN A BIOLOGICAL SYSTEM «PREGNANT WOMAN» - Галина Александровна Ушакова; Любовь Никитична Петрич (The Publishing House Medicine and Enlightenment, 2016)
Regulatory and adaptation processes are needed for the physiological development of the «pregnant woman» biological system («gravida»). Methodologically biological system «gravid» considered as a cybernetic system in which there are «inputs» and «outputs» forward and backward linkages, implemented processes and information management. One of the universal methods of communication are oscillatory processes. The system «gravida» hemodynamic fluctuations are cardiac activity and the mother of the fetus. Information is exchanged through the placenta by changing the heart rate variability of mother and fetus. The first time the definition of gravidarnogo homeostasis homeokinesis, homeorhesis, homeoclasis.